Timing of cranial suture closure in placental mammals: phylogenetic patterns, intraspecific variation, and comparison with marsupials - Rager, Lisa (2013)
Used as markers of postnatal growth closure sequences of 22 ectocranial sutures and synchondroses were recorded in a sample of 1161 skulls belonging to 38 species from all major placental clades: Afrotheria, Xenarthra, Laurasiatheria and Euarchontoglires (Boreoeutheria). The maximum closure level, which is not significantly correlated to body mass, is higher in Afrotheria and Xenarthra than in Boreoeutheria. Only the basioccipito-basisphenoid and the basioccipito-exoccipital synchondroses close in all species sampled, the supraoccipito-exoccipital and the inter-parietal sutures do in most species. Parsimov retrieved more heterochronic shifts for Afrotheria and Xenarthra than for Boreoeutheria. The amount of intraspecific variation differs among the species sampled being high among xenarthran species and low among afrotherians. Specimens (162) representing 12 marsupial genera were also analysed. Placentals exhibit a larger number of suture closures than marsupials and in both groups the sutures at the base of the skull are the first to fuse starting with the basioccipito-exoccipital.